2007
DOI: 10.1590/s0102-86502007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic intraepithelial neoplasia and ductal adenocarcinoma induced by DMBA in mice: effects of alcohol and caffeine

Abstract: Purpose:To evaluate the effects of alcohol and caffeine in a pancreatic carcinogenesis mouse model induced by 7,12-dimethylbenzantracene (DMBA), according to the PanIN classification system. Methods: 120 male, Mus musculus, CF-1 mice were divided into four groups. Animals received either water or caffeine or alcohol or alcohol + caffeine in their drinking water. In all animals, 1 mg of DMBA was implanted into the head of the pancreas. After 30 days, euthanasia was performed; excised pancreata were then fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
(26 reference statements)
0
11
0
2
Order By: Relevance
“…Interestingly, even though ethanol has been shown in a carcinogen-induced model of pancreatic cancer to enhance the development of pancreatic ductal adenocarcinomas [Wendt et al, 2007], it is still debated whether ethanol increases the risk of pancreatic cancer in humans [Gapstur et al, 2011; Michaud et al, 2010]. Since we demonstrate the differential effect of ethanol on premalignant and malignant pancreatic cells, it is possible that the varying effects of ethanol may negate the tumor promotion and inhibition effects of ethanol.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, even though ethanol has been shown in a carcinogen-induced model of pancreatic cancer to enhance the development of pancreatic ductal adenocarcinomas [Wendt et al, 2007], it is still debated whether ethanol increases the risk of pancreatic cancer in humans [Gapstur et al, 2011; Michaud et al, 2010]. Since we demonstrate the differential effect of ethanol on premalignant and malignant pancreatic cells, it is possible that the varying effects of ethanol may negate the tumor promotion and inhibition effects of ethanol.…”
Section: Discussionmentioning
confidence: 71%
“…Current animal models of pancreatic cancer include xenograft models [7][8][9] , carcinogen-induced models [10][11][12][13] , and genetically engineered models [14][15][16][17][18] . In the carcinogeninduced model, when pancreatic cancer is induced, hepatocellular carcinoma and other tumors occur simultaneously due to poor specificity of the carcinogen; thereby, the accuracy of using such animal models is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a transplacental induction model of pancreatic ductal cancer featuring NNK and EtOH treatment in the Syrian golden hamster, EtOH alone caused pancreatitis and hyperplasia, while NNK alone did not induce either [8], indicating a strong enhancing effect of pancreatitis on pancreatic carcinogenesis. It has also been reported that EtOH and nicotine promote pancreatic carcinogenesis in the DMBA-implanted mouse model [85,86]. …”
Section: Modifying Factors In the Experimental Pancreatic Carcinogenementioning
confidence: 99%